The Experience of a Drug Evaluation Committee at a University Hospital - Gómez, Ana P.; Filloy , María F.; Beragua , Roxana M.; Chiarante, Nicolás A.; Burgos, Mariana A.; Alvarez, Karina E.; Buela, Gabriela; Di Giuseppe, Luis A. (Revista del Hospital Italiano de Buenos Aires, 2025)
Introduction: The exponential development of innovative drugs poses challenges to healthcare systems in ensuring equitable access to new treatments. At the hospital level, Drug Evaluation Committees (DECs) in each institution analyze the evidence on the effectiveness, safety, and cost of new drugs and make recommendations tailored to their specific contexts. Our objective is to describe the DEC's activity at a university hospital.Materials and Methods: This cross-sectional study was undertaken at a university hospital. The evaluations made between 2017 and 2023 were analyzed. We used descriptive statistics to quantify the number of evaluation requests received, the drugs incorporated, requesting departments, and the medications' ATC classification.Results: The DEC began its activities in 2011 and is comprised of a team of 13 healthcare professionals. During the study period, 111 requests for drug inclusion were received, of which 90 (81.1%) were approved and incorporated into the institutional formulary. The Internal Medicine Department submitted 60 (54%) requests, 26 (23%) of those came from the Oncology Section.Conclusions: The DEC plays a central role in incorporating new drugs into the institutional formulary, especially in critical areas such as Oncology, addressing the growing demand for evaluating innovative treatments.
Keywords: Pharmacy and Therapeutics Committee; Technology Assessment; Pharmacy Service; Hospital Administration; Drug Committees